Щодо формули стратегії повоєнної перебудови економіки - Amosha, Oleksandr I.; Amosha, Оlena О. (Institute of Industrial Economics of NAS of Ukraine, 2023)
Despite continuing military activities, the strategy of post-war economic recovery is being developed in Ukraine. Nevertheless, the lack of clear and transparent formula of strategic transformation decreases the effectiveness of economic complex further development. The article pays attention to the fact that it is exactly infrastructure in the sense wider than merely transport and energy one, infrastructure, that includes social sphere functioning is able to become a key word to the aforementioned formula.   Economic infrastructure, being a complex of different branches and types of activities, influences directly the speed of goods and funds movement, services quantity and quality, and the dynamics of economic growth in general.At the moment the plan of transforming Ukraine into pan-energetic transiting body for all Eurasian territories, which had been offered earlier, seems to be hardly ever realistic. However, electric power networks of Ukraine and Europe happened, which needs to be taken into account while scrutinizing prospective.As is has been shown, the separate problem is underdevelopment of innovation structure in old industrial regions of Ukraine. Even now Ukraine takes the 42nd place in the world in startups implementation. The increase of regional activities in this sphere allows to sufficiently modernize the country economy and mobilize the large amount of foreign investment.The article provides examples of possible economic development in innovative, transport and energy infrastructure. Even demographic situation in the country could be improved by the relevant infrastructure transformations, in particular, by promoting «active longevity», decreasing migration loss, etc.Creation of production and social day-to-day infrastructure according to European model may well become a formula of post-war recovery strategy for Ukraine.